Analysis on Centrifugal Pump Performance in Single, Serial, and Parallel - Ansori, Faisal; Widodo, Edi (Journal of Energy, Mechanical, Material and Manufacturing Engineering, 2018)
The pump is a tool to provide the mechanical energy to the liquid in the pump constant fluid density and large. In terms of mechanism, the pump is divided into three types, namely, rotary pumps, pump the shaft/piston and centrifugal pumps. The use of the pump are the most widely used either in the household or in the environment industry. In the centrifugal pumps, there are losses – losses among other head losses. To find the head losses among other data needs head on the pump, the pump and the discharge flow rate of the pump. Head is defined as energy per unit weight of the fluid. The head of the unit (H) meters or feet is fluid. In the pump, the head is measured by calculating the difference between the total pressure of the suction pipe and the pipe press, when measurement is done at the same height. For single full pump openings 0,00246 m³ \ s, valve openings ¾ 0,00210 and aperture of ½ 0,00177 m³ \ s can be concluded the discharge of water at the pump the larger the opening of the valve the greater the discharge of its water. Moreover, vice versa, if the opening of the valve is getting smaller then the water debit is getting smaller. For full opening valves 3,11 m / s, for openings ¾ 2,65 m / s and ½ 2,23 m / s open valve openings. For the flow, velocity can be concluded the greater the opening of the valve the flow velocity is smaller and vice versa the smaller the opening of the valve the greater the flow rate. single centrifugal pump full valve openings 0.409 kg / cm², the opening of the valve ¾ 0,209 kg / cm² and the opening of the valve ½ 00,069 kg / cm² can be concluded the smaller the opening of the opening valve the smaller the head as well, and the greater the open valve opening, the more big head also in the can.